On the Topological Fundamental Groups of Quotient Spaces - Mashayekhy, B.; Pakdaman, A.; Torabi, H. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let p: X → X/A be a quotient map, where A is a subspace of X. We study the conditions under which p ∗(π 1 qtop (X, x 0)) is dense in π 1 qtop (X/A,∗)), where the fundamental groups have the natural quotient topology inherited from the loop space and p * is a continuous homomorphism induced by the quotient map p. In addition, we present some applications in order to determine the properties of π 1 qtop (X/A,∗). In particular, we establish conditions under which π 1 qtop (X/A,∗) is an indiscrete topological group.